Proceso de Atención de Enfermería en Neonato de 35 Semanas de Gestación con Enterocolitis Necrosante. - Moreira Rodríguez, Katherine Geomara (2022)
The following research work allows to promote knowledge bases related to the clinical case with the theme PROCESS OF NURSING CARE IN NEONATES OF 35 WEEKS OF GESTATION WITH NECROZING ENTEROCOLITIS. The information collected from this case was raised in the Specialty Hospital of the Armed Forces No. 1 in the city of Quito. In the present clinical case, diagnostic methodology was used to access the patient's clinical history, as well as presumptive and differential data collection, follow-up and observations. In the theoretical framework, the relevant research is carried out on the origin and prophylaxis within the hospital area, in the neonate with Necrotizing Enterocolitis. Necrotizing enterocolitis appears in neonates, mainly in premature infants, which generates necrosis in certain parts of the intestine due to inflammation; its causes are said to be unknown, however, infections are considered to be concurrent factors, as well as inadequate preparation of formula feeding. It occurs frequently in neonatal intensive care areas, with an average of 1.3 cases per thousand live newborns; approximately 85% are premature. The immediate diagnosis, as well as the timely nursing assessment, is of great importance for its treatment. Care by the nursing staff is essential because the signs and symptoms of this pathology can be fatal.